Molecular and Cytogenetic Analyses on Brazilian Youths with Pervasive Developmental Disorders - Higino Estécio, Marcos Roberto [UNESP]; Fett-Conte, Agnes Cristina; Varella-Garcia, Marileila; Fridman, Cíntia; Silva, Ana Elizabete [UNESP] (Springer Nature, 2002)
The Pervasive Developmental Disorders (PDDs) constitute a group of behavioral and neurobiological impairment conditions whose main features are delayed communicative and cognitive development. Genetic factors are reportedly associated with PDDs and particular genetic abnormalities are frequently found in specific diagnostic subgroups such as the autism spectrum disorders. This study evaluated cytogenetic and molecular parameters in 30 youths with autism or other PDDs. The fragile X syndrome was the most common genetic abnormality detected, presented by 1 patient with autism and 1 patient with PPD not-otherwise specified (PPD-NOS). One girl with PDD-NOS was found to have tetrasomy for the 15q11-q13 region, and one patient with autism exhibited in 2/100 metaphases an inv(7)(p15q36), thus suggesting a mosaicism 46,XX/46,XX,inv(7)(p15q36) or representing a coincidental finding. The high frequency of chromosomopathies support the hypothesis that PDDs may develop as a consequence to chromosomal abnormalities and justify the cytogenetic and molecular assessment in all patients with PDDs for establishment of diagnosis.
Keywords: Cytogenetic analysis; Fragile X; Genetic factors; PDD; PDD-NOS; adolescent; adult; autism; behavior disorder; Brazil; child; child behavior; chromosome 15q; chromosome aberration; chromosome inversion; chromosome mosaicism; clinical article; clinical feature; cognitive development; controlled study; cytogenetics; developmental disorder; female; fragile X syndrome; genetic disorder; heredity; human; interpersonal communication; juvenile; karyotype 46,XX; male; metaphase; neurobiology; priority journal; tetrasomy; Asperger syndrome; classification; genetic screening; genetics; karyotyping; nucleotide sequence; polymerase chain reaction; preschool child; Rett syndrome; Adolescent; Adult; Asperger Syndrome; Autistic Disorder; Child; Child Development Disorders, Pervasive; Child, Preschool; Chromosome Aberrations; DNA Mutational Analysis; Female; Fragile X Syndrome; Genetic Screening; Humans; Karyotyping; Male; Polymerase Chain Reaction; Rett Syndrome